Applied modeling of the objects in the e-laboratory environment - Bielskis, Antanas Andrius; Ramašauskas, Olegas (Lietuvos matematikos rinkinys, 2003)
An attempt to implement adaptive learning and modeling possibilities in a distance learning environment is shown in this article. Flexible learning environment means the system able not only to present and manage learning material, collect information about the users, give statistics on them and learning material, but even able to adapt its behavior to the specific learner needs. Usually standard learning environments have nothing to offer in such a case. The possibilities to use such an object in distance education and to add this experience to the knowledge base of e-learning adviser by studying informatics in Klaipėda University and Business College of Western Lithuania also discussed.